The Literacy Factor in Syntactic Judgement & Comprehension in Adults - Aparna Vijayan (Journal of All India Institute of Speech and Hearing, 1970)
The present study was undertaken to investigate the qualitative differences among normal literate and illiterate individuals on linguistic and metalinguistictasks by evaluating their performance on simple comprehension and expression tasks as well as on a grammaticality judgement task. A group of sixty healthysubjects - thirty literates and thirty illiterates - in the ages range of 22 to 40 years were selected for the study. The subjects were required to be native -Kannada speakers with no speech or hearing problems. The two groups were studied for their performance on three tasks utilizing two tests, namely theSyntactic Section of the LPT and that of the RRTC Battery aiming to evaluate the subjects' syntactic judgement ability, their comprehension and expression.A qualitative, statistical and quantitative analysis of the results was carried out.